PARTISIPASI MASYARAKAT DALAM PENANGANAN KEBERSIHAN PANTAI DI KECAMATAN MALALAYANG KOTA MANADO - SURATINOYO, SARIFA AYU; Lengkong, Florence Daicy; Londa, Very (Sam Ratulangi University, 2017)
Abstract: The problem that often arise in malalayang beach in because Malalayang Beach become one of culinarytourism object which become one of garbage supplier in coastal area of Malalayang Beach in this case there shouldbe participation from society in the form of physical donation, material contribution, and moral contribution. Basedon these issues, the participation of the community is very important in maintaining cleanliness at the beach.Departing from the importance of community participation in need in maintaining coastal cleanliness, so that theresearcher is interested to appoint and discuss and examine the title of research on Community Participation inHandling of Beach Hygiene in Kecamatan Malalayang Manado City.This research uses qualitative method because it is done in natural condition. The number of informants is 17people, consisting of one sub-district head, 1 person head, 1 neighborhood head, 4 people from local people, and10 tourists.Keywords: Community Participation, Cleanliness.